Foreign Policy Responses to the Rise of Brazil
XIV, 239 p.
Keywords: Brazil is undeniably on the rise, and its economic weight and international activism have attracted considerable attention. However, the limitations of its capacity and will to turn potential power into actual international influence are equally significant. So far, relatively little attention has been paid the diverse ways in which other Latin American countries have perceived, and responded to, the rise of Brazil. This edited volume redresses the gap by answering some crucial questions about the international relations of Latin America: what has been the real impact of the rise of Brazil on other Latin American states? What is the place of Brazil in their foreign policy? What role do extra-regional actors play? What is the weight of domestic factors? Have Latin American countries devised specific strategies to cope with the rise of Brazil? Thirteen case-study chapters answer these questions while providing thought-provoking considerations for other emerging powers and regions. .